Un aspetto particolare del plurilinguismo della societŕ italiana: il rapporto lingua vs. dialetti nell'insegnamento scolastico in Italia - Beszterda, Ingeborga (Wydawnictwo Naukowe UAM, 2008)
This article presents the issue of linguistic policy and the attitude of educational authorities towards dialects from the point of view of the multi-lingual and multiculture Italian society. Due to specific historical conditions the linguistic situation in Italy is characterized by a high degree of heterogeneity -numerous dialects exist alongside the national language. After the period of the political unity of Italy in 1861 the educational authorities have had to tackle two problems: the necessity of having to choose a linguistic norm and also mutual relations between the language and the dialects. Those issues were and still are highly controversial and are subject to heated polemics as the answer to the question of whether to accept dialects or eliminate them from school education has never been found.
The specific aspect of multi-lingual Italian society, the relation between the language and dialects in school education in Italy
Keywords: Italian language; Multi-lingual Italian society; School education